Water droplet behavior in between hydrophilic and hydrophobic surfaces and dust mitigation. Issue 44 (10th October 2022) - Yilbas, Bekir Sami; Abubakar, Abba Abdulhamid; Adukwu, Johnny Ebaika; Hassan, Ghassan; Al-Qahtani, Hussain; Al-Sharafi, Abdullah; Unal, Muhammet; Alzaydi, Ammar
Abstract : An innovative method is introduced for environmental dust mitigation from a hydrophobic surface by a sessile water droplet. Abstract : An innovative method is introduced for environmental dust mitigation from a hydrophobic surface by a sessile water droplet. The sessile water droplet is located between two parallel plates having hydrophilic (at the top) and hydrophobic (at the bottom) states. The water droplet is located at the top hydrophilic plate, and the effect of the plate spacing on dust mitigation rate is examined. The droplet behavior is analyzed for different plate spacings and various droplet sizes using a high-speed camera. The fluid and the particle motions are simulated inside the droplet while adopting the experimental conditions. The findings demonstrate that the sessile droplet can effectively mitigate dust. Reducing the plate spacing increases the droplet meniscus diameter and enhances the dust removal rate. The surface tension force on the hydrophilic surface remains greater than that of the pinning force on the dusty hydrophobic surface even though the Magdeburg and surface tension forces contribute to the droplet pinning force on the hydrophobic dusty surface. Flow current is developed in the droplet fluid during the squeezing period, which considerably enhances the dust removal rate from the hydrophobic surface. The cleaned area increases with the droplet volume and plate spacing. Stria patterns are observed on the circumference of the dust-removed area. The present study provides a detailed analysis of a new method of dust removal from surfaces for self-cleaning applications.